EKSPLORASI INOVASI PEMBELAJARAN BAHASA INDONESIA BERDIFERENSIASI MELALUI PENDEKATAN TEACHING AT THE RIGHT LEVEL (TaRL) DI SEKOLAH DASAR - Latif, Azminudin; Markhamah; Laili Etika Rachmawati; Minsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to explore Indonesian language learning innovation based on Teaching at the Right Level (TaRL) approach in grade 4 elementary school. This research uses a qualitative approach with a case study type. The research was conducted at SDN 03 Tunggulrejo with the principal and fourth grade teacher as the subjects. Data were collected through interviews, observation, and documentation. Data validity using triangulation of sources and techniques. Data were analyzed using the Miles and Huberman interactive model. The results showed that the form of differentiated Indonesian learning innovation based on TaRL includes: (1) initial ability tests; (2) student grouping based on initial ability tests; (3) teaching materials or materials according to the needs and readiness of students (4) varied learning methods to meet the needs of diverse students; (5) varied media and learning resources (contextual and technology-based) to meet the needs and learning styles of diverse students; (6) formative tests to determine material understanding according to student abilities It is concluded that the TaRL approach emphasizes differentiation in planning, implementing, and evaluating learning to suit the needs and abilities of diverse students.